Biography writing in English as a foreign language - Otto, Justin (My University, 2014)
This paper examines narrative writing in English as a foreign language (EFL) classrooms, and then presents a series of lesson plans for teaching how to write biographies as factual narratives. These lesson plans would appear in a writing class for students attending a university in East Asia. While my interest in this subject stems from my background in social work, the specific requirements for similar writing tasks in healthcare and human services professions are not addressed here. Instead, I am providing a general approach to writing biographies, and this provides a foundation for other tasks such as providing written background information about elderly patients. In human services settings, it is uncommon to write about someone as illustrious as Audrey Hepburn, but she is the sample subject in my lesson plans. As an enduring cultural icon, Hepburn's image is already familiar to English students in many parts of the world. Hepburn is also chosen here to help students understand that the fame of an individual should not interfere with an accurate account of this individual's life. In the genre of biography any subject is held to the same rules: in the words of Leon Edel, "the biographer who worships his hero blinds himself to the meaning of his material."
Plan B Paper. 2014. Master of Arts-TESOL--University of Wisconsin-River Falls. English Department. 65 leaves. Includes bibliographical references (leaves 62-65).
Keywords: English language--Study and teaching--Foreign speakers; English language--Composition and exercises--Study and teaching--Foreign speakers